The need for closeness and intimacy and disability awareness - Joanna Konarska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article touched the aspect of intimate relationships emotional young people with disabilities, are described some difficulties in learning the correct emotional relationships with their mothers and others in early childhood. These difficulties, however, are not directly related to the disability, but rather are the result of parents' reaction to the unusual and therefore not always "clear" for the parents reaction emotional and social child. Messages emotional child are wrongly perceived by the other members of society, which expands the circle as they grow, and this situation contributes to the abnormal emotional and social relationship between the person with a disability and the environment. However, the emotional needs are the same for people with and without disabilities, but in the context described disturbances in interpersonal relationships, can not always be met. This applies especially to the need for a close emotional relationship with a person of the opposite sex during adolescence and early adulthood, when these types of needs are particularly severe. The research shows that many young people see a solution to this problem in touch and finding a life partner through the Internet.